Assessment of Oxidative Stress-Induced DNA Damage by Immunoflourescent Analysis of 8-OxodG - Lee, S.; Pervaiz, Shazib (2011)
Oxidative stress refers to the imbalance between the generation of reactive oxygen species (ROS) and their scavenging by the inherent antioxidant defenses of the cell. The abnormal accumulation of ROS is the underlying pathology in a variety of human diseases such as neurodegenerative phenomena, inflammatory diseases, metabolic disorders, and cancer. The mechanism by which abnormal accumulation of ROS contributes to pathological conditions involves damage or oxidative modification of biomolecules, such as nucleotides, lipids, and proteins. One of the most common targets of ROS is DNA, modifications of which have been associated with cellular transformation and genome instability. There are a number of experimental strategies to assess oxidative modification of DNA bases, such as chromatography-based assays and indirect immunofluorescence. While the former provide quantitative assessment of oxidative modification, the latter is a much simpler assay for qualitative determination of DNA base modification in very small sample sizes. Here, we present a brief background of the various methodologies for the assessment of a specific oxidative DNA modification, 8oxodG, and present a more detailed account of the indirect immunofluorescence assay. © 2011 Elsevier Inc.